2006
DOI: 10.1016/j.jvs.2005.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the peroxynitrite-poly(adenosine diphosphate-ribose) polymerase pathway during neointima proliferation: A new target to prevent restenosis after endarterectomy

Abstract: Pharmacologic inhibition of PARP with INO-1001 may be a new concept to prevent neointimal hyperplasia after endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…These results are not surprising, based on our previous data showing that PD128763 was unable to block SMC proliferation or migration in response to growth factor stimulation (Yau et al, 2003). In addition, these data suggest that ischemic injury is not a component of the vascular repair process, as has been previously suggested (Beller et al, 2006), although induction of hypoxia-inducible factor-1␣ after angioplasty has been observed (Karshovska et al, 2007). The slight inhibition in neointimal formation obtained with 3AB was concluded to represent inhibition of ART rather than PARP, as would be expected with the concentration that was used (Yau et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…These results are not surprising, based on our previous data showing that PD128763 was unable to block SMC proliferation or migration in response to growth factor stimulation (Yau et al, 2003). In addition, these data suggest that ischemic injury is not a component of the vascular repair process, as has been previously suggested (Beller et al, 2006), although induction of hypoxia-inducible factor-1␣ after angioplasty has been observed (Karshovska et al, 2007). The slight inhibition in neointimal formation obtained with 3AB was concluded to represent inhibition of ART rather than PARP, as would be expected with the concentration that was used (Yau et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…19 Furthermore, PARP inhibition was shown to prevent neointimal hyperplasia after endarterectomy. 28 Therefore, it is conceivable that the effects of PARP inhibition on plaque number and size observed in the present study may be due in part to protective effects against endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 77%
“…19,28 Indeed, the early atherosclerotic functional alterations that develop in the endothelium of the ApoE Ϫ/Ϫ mice were shown to be dependent on the activation of PARP in endothelial cells. 19 Furthermore, PARP inhibition was shown to prevent neointimal hyperplasia after endarterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, evidence is growing that reduced nitric oxide (NO)-cyclic guanosine monophosphate (cGMP) signaling plays an important role in the pathogenesis of neointima formation, 8 which could be prevented by local delivery of NO 9 or by using a short-acting NO donor in the perivascular area of the injured rat carotid artery.…”
mentioning
confidence: 99%
“…6 Our previous studies showed that nitro-oxidative stress plays an important role in neointima formation after vascular injury, which could be effectively decreased by the inhibition of the peroxynitrite-poly (adenosine diphosphateribose) polymerase (PARP) pathway. 7 In addition, evidence is growing that reduced nitric oxide (NO)-cyclic guanosine monophosphate (cGMP) signaling plays an important role in the pathogenesis of neointima formation, 8 which could be prevented by local delivery of NO 9 or by using a short-acting NO donor in the perivascular area of the injured rat carotid artery. 10 Furthermore, neointimal proliferation could also be attenuated by endothelial NO synthase gene transfer in a rat model of balloon injury.…”
mentioning
confidence: 99%